Второй фронт – 70 лет - Гадеев, А.В. (Культура народов Причерноморья, 2014)
В статье анализируется открытие второго фронта, высадка союзных войск на северо-
западном побережье Франции, в Нормандии. Союзники имели подавляющее превосходство в силах.
Высадка союзников в Нормандии (операция «Оверлорд») оказалась для немецкого командования полной
неожиданностью. В середине июня 1944 г. состоялся первый обстрел Лондона ракетами ФАУ-1, ФАУ-2.
Союзники имели конкретный перевес в танках и самолетах. В Германии происходит попытка
государственного переворота, покушение на Гитлера. В ходе сражения за Францию немецкие войска
потерпели сокрушительное поражение. У статті аналізується відкриття другого фронту, висадка союзних військ на північно-
західному узбережжі Франції, в Нормандії. Союзники мали перевагу в силах. Висадка союзників у
Нормандії (операція «Оверлорд») виявилася для німецького командування повною несподіванкою. У середині
червня 1944 р. відбувся перший обстріл Лондона ракетами ФАУ-1 та ФАУ-2. Союзники мали конкретну
перевагу в танках і літаках. В Німеччині відбувається спроба державного перевороту, замах на Гітлера.
Підчас битви за Францію німецькі війська зазнали нищівної поразки. The article analyzes the opening of the second front, the landing of the allied troops on the Northwest
coast of France, in Normandy. The allies had an overwhelming superiority in forces. The landing of the allies in
Normandy (operation overlord) was for the German command complete surprise. In mid-June 1944-the first
bombardment of London missiles V-1, V-2. The allies had a clear advantage in tanks and aircraft. In Germany, is a
coup d'etat, the attempt on Hitler's life. During the battle for France German army suffered a crushing defeat.
The plight of Germans at the front exacerbated by the disruption of their top commanders. The landing of the allies
in Normandy and the defeat of the German troops in Belarus caused a political crisis in Germany. He put it in a
coup attempt, which was organized dissatisfied with Hitler's military. The conspirators were supposed to physically
eliminate the Fuhrer, to seize power, and then to make peace with all countries of anti-Hitler coalition.